1988
DOI: 10.1152/ajprenal.1988.254.4.f463
|View full text |Cite
|
Sign up to set email alerts
|

Role of prostaglandins in protein-induced glomerular hyperfiltration in normal humans

Abstract: In six healthy male volunteers we studied the effect of indomethacin on the renal hemodynamic adaptations to an acute oral protein load. Control and protein loading studies without and with indomethacin were performed under sustained water diuresis. In the control studies without indomethacin, creatinine (CCr) and inulin clearance (CIn) remained stable and p-aminohippurate (PAH) clearance (CPAH) and kaliuresis slightly decreased while natriuresis progressively increased. Urinary prostaglandin E2 (PGE2) excreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…This interest mainly reflects the genesis of the hy perfiltration model advanced by Brenner et al [1] for the understanding of progression in renal disease. Although the mechanism by which GFR increases following a protein load still remains unknown, it is now widely accept ed that it depends on increased ultrafiltration pressure and that its nature is hormonal [2][3][4][5][6][7][8]. Furthermore, the possibility that the changes in GFR which follow the variations in protein intake may reflect changes in the tubuloglomerular feedback mechanism has been ex plored by indirect clearance [9] techniques, which have disclosed the possibility that the increase in GFR may reflect proximal hyper reabsorption as well as inhibition of distal re absorption.…”
Section: Introductionmentioning
confidence: 99%
“…This interest mainly reflects the genesis of the hy perfiltration model advanced by Brenner et al [1] for the understanding of progression in renal disease. Although the mechanism by which GFR increases following a protein load still remains unknown, it is now widely accept ed that it depends on increased ultrafiltration pressure and that its nature is hormonal [2][3][4][5][6][7][8]. Furthermore, the possibility that the changes in GFR which follow the variations in protein intake may reflect changes in the tubuloglomerular feedback mechanism has been ex plored by indirect clearance [9] techniques, which have disclosed the possibility that the increase in GFR may reflect proximal hyper reabsorption as well as inhibition of distal re absorption.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a previous study suggested that people with diabetes may have an enhanced glomerular hyperfiltration response to glucagon infusion (40). Vasodilatory prostaglandins may be required for the renal hemodynamic responses to glucagon or amino acids, but this finding has been variable (12,21,33,46,59). The main objectives of this study were to evaluate whether glucagon mediates the augmented glomerular hyperfiltration response to amino acids in diabetes and whether the responses to amino acids and glucagon depend on prostaglandins.…”
mentioning
confidence: 99%
“…By contrast, Krishna et al [3] and Vanrenterghem et al [4] found an attenuated/ blunted response to a meat meal after prostaglandin sup pression. Furthermore, following intravenous amino acid administration, cyclo-oxygenase inhibitors suppressed the rise in renal plasma flow (RPF) and glomerular filtration rate (GFR); however, amino acid infusion in the control Accepted: March 12,1993 study and in the study where amino acids had been given before the administration of cyclo-oxygenase inhibitors did not increase the urinary excretion of 6-keto-prostaglandini" (PGF|,() [5].…”
Section: Introductionmentioning
confidence: 89%